Sukuk, bond market development and target capital structure : selected Southeast Asian Countries - Haron, Razali; Ibrahim, Khairunisah; Abdul Razak, Dzuljastri (2012)
This study aims to identify the existence of target capital structure and explore firm specific and country specific determinants of target capital structure for firms in the selected Southeast Asian countries (Malaysia, Thailand and Singapore). We detect a remarkable effect of bond market development on capital structure of firms in Malaysia comparative to Thailand and Singapore. This study argues that this is due to the development of sukuk, or Islamic bonds in Malaysia. The distinctive effect of bond market development with sukuk element on Malaysian firms shows that institutional environment and governance in which the firm operates do influence the capital structure decision. This study contributes to the existing literature by highlighting the impact of sukuk on bond market development as one of the significant determinants of target capital structure via the dynamic model.